2021
DOI: 10.1186/s12885-021-08662-2
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of immune checkpoint inhibitor therapy in advanced lung cancer

Abstract: Background The advent of immune checkpoint inhibitors (ICIs) therapy has resulted in significant survival benefits in patients with non-small-cell lung cancer (NSCLC) without increasing toxicity. However, the utilisation of immunotherapy for small-cell lung cancer (SCLC) remains unclear, with a scarcity of systematic comparisons of therapeutic effects and safety of immunotherapy in these two major lung cancer subtypes. Herein, we aimed to provide a comprehensive landscape of immunotherapy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Immune checkpoint inhibitors (ICIs), including anti-programmed cell death-1 (PD-1)/programmed death-ligand 1 (PD-L1) drugs (such as nivolumab, pembrolizumab, and atezolizumab) and anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4) agents (ipilimumab), have become key treatments for patients with advanced or recurrent non-small-cell lung cancer (NSCLC) [ 25 ]. In addition, most patients with advanced NSCLC receive ICIs as a first-line combination chemoimmunotherapy in clinical settings worldwide [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs), including anti-programmed cell death-1 (PD-1)/programmed death-ligand 1 (PD-L1) drugs (such as nivolumab, pembrolizumab, and atezolizumab) and anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4) agents (ipilimumab), have become key treatments for patients with advanced or recurrent non-small-cell lung cancer (NSCLC) [ 25 ]. In addition, most patients with advanced NSCLC receive ICIs as a first-line combination chemoimmunotherapy in clinical settings worldwide [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now, chemotherapy combined with immunotherapy is the standard treatment for lung cancer, except for patients with high PD-L1 expression(Maung et al 2020). Our ndings indicate that combining chemotherapy with immunotherapy, compared to immunotherapy alone, enhances progression-free survival and OS for patients(Wang et al 2021). D-dimer, a product of brin degradation, re ects brinolysis function.…”
mentioning
confidence: 73%
“…Many studies have shown that they are involved in altering the ability of the immune system to recognize malignant cells. In conditions of immune homeostasis, immune checkpoints provide self-tolerance by maintaining T lymphocyte activation, which causes inhibition of the immune response, but in the case of cancer, they are inhibited and the immune system is reactivated so that it is able to launch an attack on cancer cells [ 350 , 351 ]. In the literature, we found data on the detailed mechanisms of action of almost 20 significant modulators of immune checkpoints ( Table 4 ), such as LAG-3, TIM3 and TIGIT, as well as the programmed cell death receptor 1 (PD-1) and a protein associated with cytotoxic T-4 lymphocytes (CTLA-4) ( Figure 5 ), which have found their greatest application in clinical practice, including the treatment of lung cancer [ 350 , 351 , 352 , 353 , 354 , 355 ].…”
Section: Resultsmentioning
confidence: 99%
“… Exemplary interactions between a T lymphocyte and a tumor cell and dendritic cell, including immunological checkpoints (based on [ 350 , 351 , 352 , 353 , 354 , 355 ]). …”
Section: Figurementioning
confidence: 99%